Pengaruh Ukuran Perusahaan dan Likuiditas Terhadap Struktur Modal Dengan Profitabilitas Sebagai Variabel Intervening - Wahyuningsih, Wahyuningsih; Meliza, Meliza; Mahirun, Mahirun (DAS Institute, 2025)
The food and beverage sector is one of the industries that plays a strategic role in supporting economic growth in Indonesia. The growth of this sector is driven by high domestic demand and government support through policies that promote the development of the food and beverage industry. The objective of this research is to identify and analyze the effect of firm size and liquidity on capital structure, with profitability as an intervening variable, in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research employs a quantitative approach. The sample consists of 14 food and beverage companies listed on the IDX during the 2019-2023 period. Data collection techniques use secondary data in the form of annual reports from 2019-2023. The data analysis methods include descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS tools. The results of this study indicate that firm size and liquidity have a significant negative effect on capital structure, while profitability has an insignificant negative effect on capital structure. Firm size and liquidity significantly negatively affect capital structure, with profitability as an intervening.